2018
DOI: 10.1101/308528
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-omic profiling of tyrosine kinase inhibitor-resistant K562 cells suggests metabolic reprogramming to promote cell survival

Abstract: The authors declare no conflict of interest. Multi-omic profiling of tyrosine kinase inhibitor-resistant K562 cells suggests metabolicreprogramming to promote cell survival Key Points:• Alterations to metabolism are a common feature of target-mutation-independent resistance in CML cells across multiple clinically relevant TKIs.• Carbonic anhydrase 1 (CA1) and a-synuclein (SNCA) are novel markers of metabolic reprogramming in TKI resistant CML cells. AbstractResistance to chemotherapy can occur through a wide v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…22 Multi-omics analysis of tyrosine kinase inhibitor-resistant K562 cells indicated that metabolic reprogramming promotes cell survival. 23 Chandran RK study A B Figure 16 HE staining of the tumor (A is the control group, the long arrows point to muscle infiltration, B is the treatment group, the short arrows point to the ischemic necrosis, ×200). Figure 17 HE staining of mouse liver and spleen (A is the liver of the control group, B is the liver of the treatment group, C is the spleen of the control group, D is treatment group spleen, ×200).…”
Section: Discussionmentioning
confidence: 99%
“…22 Multi-omics analysis of tyrosine kinase inhibitor-resistant K562 cells indicated that metabolic reprogramming promotes cell survival. 23 Chandran RK study A B Figure 16 HE staining of the tumor (A is the control group, the long arrows point to muscle infiltration, B is the treatment group, the short arrows point to the ischemic necrosis, ×200). Figure 17 HE staining of mouse liver and spleen (A is the liver of the control group, B is the liver of the treatment group, C is the spleen of the control group, D is treatment group spleen, ×200).…”
Section: Discussionmentioning
confidence: 99%